Quizizz Based Application in Teaching Reading in an Indonesian EFL Junior High School Context - Nurhaya, Nurhaya; Abduh, Amirullah (Fakultas Sastra - Universitas Muslim Indonesia, 2023)
This study employs a case study design with a qualitative descriptive approach that aimed to shed light on; (1) the teachers’ perception on Quizizz in teaching reading, (2) the implementation of Quizizz in teaching reading and, (3) the impacts of Quizizz on students’ reading comprehension. The participants of this research were three teachers selected through purposive sampling. The instruments used were observation, interview and teachers’ documents. The findings of this research revealed that; (1) stemming on teachers’ interview, teachers’ perception on Quizizz in teaching reading was classified into two categories namely highly and moderately perceived on Quizizz in teaching reading. Furthermore, (2) the implementation of Quizizz in teaching reading was classified into two categories namely moderately implemented and lowly implemented in utilizing Quizizz in teaching reading. Finally, (3) the findings had shown that Quizizz had positive impacts on students’ reading comprehension in literal level, inferential level, critical level and creative level. The findings of this study underline the potential of digital applications like Quizizz in revolutionizing the pedagogical approach in Indonesian EFL classrooms, particularly in the teaching of reading skills.